Interpretative Analysis of Divine Assistance Verses in Ayatollah Khamenei’s Quranic Thought With Emphasis on the Verses “Indeed, Allah will surely support those who support Him” and “If you support Allah, He will support you” - Sajjad Mohammadfam; Hadi Ghafari Iri Uliya (قرآن فرهنگ و تمدن)
This article examines the tradition of divine assistance (nusrat-e ilāhī) in the Quranic thought of Ayatollah Khamenei, the Leader of the Islamic Republic of Iran. The concept of divine assistance, as presented in the two verses “Indeed, Allah will surely support those who support Him” and “If you support Allah, He will support you” (Quran 22:40, 47:7), emphasizes God’s support for those who strive for truth. The significance of analyzing Ayatollah Khamenei’s interpretation of these verses lies in its impact on foreign policy, its inspirational role for religious communities, its elucidation of the relationship between religion and politics, and its relevance in understanding contemporary challenges. This study employs a descriptive-analytical approach, systematically extracting, classifying, and analyzing instances where these verses appear in Ayatollah Khamenei’s speeches and writings. The findings reveal that, in his view, supporting religion encompasses multiple dimensions beyond military jihad, extending to intellectual, scientific, and cultural efforts. He also interprets divine assistance to believers as comprising both material and spiritual aid, often manifesting in unexpected ways. Instances of divine assistance in the contemporary era include the establishment of the Islamic Republic of Iran, victory in the imposed war (Iran-Iraq War), and the emergence of the Islamic awakening movement. The outcomes of divine assistance are dignity, unity, and power. Furthermore, the relationship between supporting divine religion and divine support for believers is asymmetrical, with ultimate victory granted to the collective body of the faithful.